2016
DOI: 10.3168/jds.2015-9472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rice bran as a replacement for oat grain in energy and nitrogen balance, methane emissions, and milk performance of Murciano-Granadina goats

Abstract: The objective of this experiment was to study the effects of substituting oat grain with rice bran on energy, nitrogen and carbon balance, methane emissions, and milk performance in dairy goats. Ten Murciano-Granadina dairy goats in late lactation (46.1 ± 3.07 kg) were assigned to 2 treatments in a crossover design, where each goat received both treatments in 2 periods. One group of 5 goats was fed a mixed ration with 379 g of oat grain/kg of dry matter (O diet) and the other group of 5 goats was fed a diet th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…No differences between treatments were observed for MEI (998 ± 29.5 kJ/kg of BW 0.75 , on average), although our values were lower than other (1,254 kJ MEI/kg of BW 0.75 for Murciano-Granadina goats [Criscioni and Fernández, 2016] and 1,126 kJ MEI/kg of BW 0.75 for Saanen goats [Bava et al, 2001]), both at late lactation. Criscioni and Fernández (2016) used mixed diets with similar forage:concentrate ratio (35:65) than the present study. The concentrate and premix were pelleted, although the forage was alfalfa hay not pelleted.…”
Section: Energy Balancecontrasting
confidence: 79%
See 1 more Smart Citation
“…No differences between treatments were observed for MEI (998 ± 29.5 kJ/kg of BW 0.75 , on average), although our values were lower than other (1,254 kJ MEI/kg of BW 0.75 for Murciano-Granadina goats [Criscioni and Fernández, 2016] and 1,126 kJ MEI/kg of BW 0.75 for Saanen goats [Bava et al, 2001]), both at late lactation. Criscioni and Fernández (2016) used mixed diets with similar forage:concentrate ratio (35:65) than the present study. The concentrate and premix were pelleted, although the forage was alfalfa hay not pelleted.…”
Section: Energy Balancecontrasting
confidence: 79%
“…The ALF diets presented greater (P < 0.05) energy losses in CH 4 than LEM diet, indicating that increasing the level of lipids in diet reduced the CH 4 production, as suggested by Knapp (2014). No differences between treatments were observed for MEI (998 ± 29.5 kJ/kg of BW 0.75 , on average), although our values were lower than other (1,254 kJ MEI/kg of BW 0.75 for Murciano-Granadina goats [Criscioni and Fernández, 2016] and 1,126 kJ MEI/kg of BW 0.75 for Saanen goats [Bava et al, 2001]), both at late lactation. Criscioni and Fernández (2016) used mixed diets with similar forage:concentrate ratio (35:65) than the present study.…”
Section: Energy Balancementioning
confidence: 39%
“…The higher fat content in BB animals' milk (5.02%) was due to its lower milk yield, also related to the higher NEFA content observed, so it indicated a greater tendency for a negative energy balance, probably due to a greater mobilisation of body reserves [42]. Even though the level of NEFA in AP animals was similar to that in BB animals (0.868 mmol/L), the higher milk yield (2.21 kg/day) of the AP group meant that fat concentration was higher in the BB group than the AP group.…”
Section: Body Weight and Milk Performancementioning
confidence: 90%
“…Moreover, Tovar-Luna et al (2010) investigated Alpine goats during lactation and found values ranging from 0.62 to 0.68. Recently, Criscioni and Fernández (2015) found values of 0.72 for lactating goats at mid lactation when feeding mixed diets.…”
Section: Energy Balance and Oxidation Of Nutrientsmentioning
confidence: 97%